THE ROLE OF HUMAN CAPITAL IN THE DEVELOPMENT OF THE COUNTRY'S ECONOMY - З. К. Рахимов (American Journals, 2023)
The article describes the theoretical and practical aspects of human capital in the development of the country's economy. The data was compiled based on the author's observations and analysis of foreign literature.
Keywords: Human capital, management, structure, system, education, advanced training, efficiency, effective, factor, quality, competition, commerce, network, development, employment, infrastructure